2002
DOI: 10.1111/j.1574-6968.2002.tb11090.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus nidulans sodVIC1mutation causes defects in cell wall biogenesis and protein secretion

Abstract: Growth at the restrictive temperature (42 degrees C) of Aspergillus nidulans B120, carrying the conditional-lethal mutation sod(VI)C1, was partially improved by the addition of 1.0 M sorbitol to the medium. The mutant grown at 42 degrees C, with osmotic stabilizer, showed abnormal hyphal morphology, a decrease in beta-1,3-glucan synthase activity as well as cell wall sugar content, but an increase in chitin synthase activity and N-acetyl-glucosamine content. The mutation also affected the secretion of extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our previous study showed that the C-terminal domains of both α-COP and ε-COP are essential for their interaction, and that the N-terminal WD40 motif of α-COP and the TPR region of ε-COP are involved in controlling the interaction between these two COPs in A. nidulans [ 16 ]. We also reported that A. nidulans α-COP can substitute for S. cerevisiae α-COP functions in vivo [ 15 ]. In yeast, ε-COP is known to stabilize the thermo-sensitive α-COP mutation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed that the C-terminal domains of both α-COP and ε-COP are essential for their interaction, and that the N-terminal WD40 motif of α-COP and the TPR region of ε-COP are involved in controlling the interaction between these two COPs in A. nidulans [ 16 ]. We also reported that A. nidulans α-COP can substitute for S. cerevisiae α-COP functions in vivo [ 15 ]. In yeast, ε-COP is known to stabilize the thermo-sensitive α-COP mutation.…”
Section: Resultsmentioning
confidence: 99%
“…In Aspergillus nidulans , α-COP is essential for viability. However, like in yeast, a mutation in A. nidulans α-COP gene results in a temperature-sensitive defect in growth, cell-wall construction, and protein secretion [ 14 , 15 ]. Interestingly, the temperature dependent-osmo-sensitive phenotype of the S. cerevisiae α-COP mutant is suppressed by introduction of the A. nidulans sod VI C (stabilization of disomy) gene for α-COP [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In A . nidulans , the α-COP protein Sod VI Cp plays a role in cell wall synthesis and protein secretion by affecting β-glucan synthase activity [32]. Moreover, S .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical analysis of the composition of the cell wall was performed using the method described previously [ 14 ]. Sensitivity toward cell wall-perturbing agents was investigated via the method described by Kovács et al [ 5 ] using media supplemented with Calcofluor white (CFW) or Congo red (CR).…”
mentioning
confidence: 99%